Experimental Design of Shadow Formation in Optical Devices with 2D Algodoo Simulation - Resmiyanto, Rachmad; Lestari, Novi Ayu (UIN Sunan Gunung Djati Bandung, 2024)
The process of image formation in optical instruments such as the eye, magnifying glass, microscope, telescope, and camera is an important part of learning geometric optics. These concepts are often considered difficult and abstract by students, as the path of light and the process of image formation cannot be directly observed. The conceptual experimental method is used to identify the physical concepts in optical phenomena and translate them into 2D simulations in Algodoo. This study consists of three steps: (1) designing an experiment using Algodoo to model the image formation phenomenon, (2) configuring optical instruments, light sources, rays, and lenses to achieve image formation that aligns with its physical concepts, and (3) conceptually analyzing the simulation results and observing students while using the simulation. The results of the study show that this image formation experiment can be easily understood by students. This is evidenced by the fact that students were able to independently conduct the image formation simulation. Therefore, it can be concluded that the 2D simulation software Algodoo can be used effectively to design image formation experiments in optical instruments.